Programmed cell death-1 inhibitor-related sclerosing cholangitis: A systematic review - Onoyama, Takumi (World J Gastroenterol, 2020)
BACKGROUND: Programmed cell death-1 (PD-1) inhibitor has been indicated for many types of malignancies. However, these inhibitors also cause immune-related adverse events. Hepatobiliary disorder is a phenotype of immune-related adverse event affecting 0%–4.5% of patients treated with PD-1 inhibitors. Recent studies have reported PD-1 inhibitor-related sclerosing cholangitis (SC); however, the associated clinical and pathological features are unclear. AIM: To evaluate the clinical and pathological features of PD-1 inhibitor-related SC through a systematic review of the literature. METHODS: The review, conducted using electronic databases in PubMed, was restricted to the period from January 2014 to September 2019 and focused on case reports/series on PD-1 inhibitor-related SC published in English. We scanned the references of the selected literature to identify any further relevant studies. Six cases previously studied by us, including three that have not yet been published, were included in this review. RESULTS: Thirty-one PD-1 inhibitor-related SC cases were evaluated. Median age of patients was 67 years (range, 43–89), with a male to female ratio of 21:10. The main disease requiring PD-1 inhibitor treatment was non-small cell lung cancer. Agents that caused PD-1 inhibitor-related SC were nivolumab (19 cases), pembrolizumab (10 cases), avelumab (1 case), and durvalumab (1 case). The median number of cycles until PD-1 inhibitor-related SC onset was 5.5 (range, 1–27). Abdominal pain or discomfort (35.5%, 11/31) was the most frequent symptom. Blood serum tests identified liver dysfunction with a notable increase in biliary tract enzymes relative to hepatic enzymes, and a normal level of serum immunoglobulin G4. Biliary dilation without obstruction (76.9%, 20/26), diffuse hypertrophy of the extrahepatic biliary tract (90.5%, 19/21), and multiple strictures of the intrahepatic biliary tract (30.4%, 7/23) were noted. In 11/23 (47.8%) cases, pathological examination indicated that CD8+ T cells were the dominant inflammatory cells in the bile duct or peribiliary tract. Although corticosteroids were mainly used for PD inhibitor-related SC treatment, the response rate was 11.5% (3/26). CONCLUSION: Some clinical and pathological features of PD-1 inhibitor-related SC were revealed. To establish diagnostic criteria for PD-1 inhibitor-related SC, more cases need to be evaluated.